Continuing Monitoring in Respiratory Intensive Care Unit and Mortality in Patient Post Bronchoscopy Procedure - Vina Fiqria; Kevin Aristyo; Rasmin Menaldi (Respiratory Science, 2023)
Background: Bronchoscopy is a relatively safe procedure in the diagnosis and therapy of lung disease, however in some cases complications can occur which lead to further monitoring in the intensive care or respiratory intensive care unit (RICU) and even lead to mortality. This study aimed to determine the need for intensive care unit monitoring and the risk factors that increase the need for intensive care unit monitoring followed by mortality after bronchoscopy procedure. Method: A retrospective data of consecutive bronchoscopy procedures in Persahabatan Hospital between July to December 2021. Results: From 410 patients underwent bronchoscopy procedures, there were 52 patients (12.6%) were admitted to RICU after bronchoscopy. From patients who were treated in RICU 3 (5.8%) of them died. Patients who died during monitoring in intensive care unit had an older mean age of 60.3 years. There were 2 (12.5%) died after bronchoscopy procedures with two or more intervention, 1 patients (3%) died in the group with one intervention. There were 2 patients (13.3%) died with two or more comorbidities and 1 patient (5.9%) died with one comorbid. In the group with diagnosis of malignancy, 3 patients (7.5%) died. Whereas in patients who were performed surgery during bronchoscopy there were 2 patients (20%) died and only 1 patient (2.4%) died without any surgery during bronchoscopy. Conclusion: Although bronchoscopy is a relatively safe procedure but the need of monitoring in intensive care after bronchoscopy procedures were relatively high and mortality quite high compare to previous study. Further research is needed to determine the risk factors that increase the need of continuing monitoring in intensive care unit followed by mortality after bronchoscopy procedure.